Professional ethics and social responsibility in Algerian media legislation (Numerus academy review, 2026)
This paper seeks to highlight Algerian media legislation and its relationship tosocial responsibility in light of respect for the so-called ethics of the profession ofjournalism, through a legal reading of the media laws issued in Algeria (Law 1982 / Law 1990 / Law 2012 / Law 2014 ( to find out what If the Algerian legislator paid sufficient attention to the ethics of the profession in light of the chaos and excesses witnessed by theAlgerian media and the deterioration of the performance of the press working . The analytical study concluded that the issue of journalistic ethics did not take anappropriate place in the Algerian legislation, and there is still ambiguity surrounding many articles included in the media laws in Algeria.